Numerical investigation of the effect of spoiler’s configuration on wake vortex - Omar, Ashraf Ali E.; Asrar, Waqar; Ludin @Jamaluddin, Hani (2012)
A numerical investigation was undertaken to study the aerodynamic characteristics of wake vortices generated from an aircraft during taking-off or landing, and thus exploring the possible techniques of reducing hazard imposed to the following aircraft by means of passive wake vortex alleviation by using delta wing (DW) as an add-on device. Simulations were performed using RANS turbulence model.